EFEKTIVITAS METODE DEMONSTRASI DALAM MENINGKATKAN KETERAMPILAN VOKASIONAL MEMBUAT SNACK BOUQUET BAGI ANAK TUNARUNGU KELAS XI SMALB DI SLB PEDULI ANAK BANGSA PAYAKUMBUH - ., Widianovita; ., Armaini (Inspiratif Pendidikan, 2021)
This research discusses the problems found by the author in Payakumbuh Children’s Care Special School. This research describes how learning skills that have not had any new innovations or new skills given to children so that children start to get bored with the same skills that are learned such as gardening, sewing, and making tissue boxes from drink bottles. In connection with these problems, the author tries to provide types of vocational skills in different ways, different forms and by generating selling points that can help deaf students themselves after they finish their education, namely by presenting vocational skills to make Snack Bouquet. This research uses experimental research. The method used to determine whether the demonstration model could be effectively used in making snack bouquet skills. The subjects of this study were deaf children in class XI at Payakumbuh Children’s Care School, consisting of 3 girls and 2 boys. The result of this research is that there is an increase in the child’s ability to make snack bouquets after being given treatment using a demonstration model proven by the Wilcoxon Sign Rank Test the resulting value is 2.041 with probability and Asymp sign. (2-tailed) = 0.041 so that the probability obtained is 0.041 <0.05, thus Ho is rejected and Ha is accepted so that the demonstration method is effective to improve vocational skills in making snack bouquets for deaf class XI children at SLB Peduli Anak Bangsa Payakumbuh.